Isotropic shrinkage of the oxygen octahedron in SrTiO3 under uniaxial pressure. (23rd August 2017) - Lu, Cong; Temba, Chisato; Nakajima, Nobuo; Kawakami, Shuhei; Ishimatsu, Naoki; Maruyama, Hiroshi
Abstract: X-ray absorption spectra at the Ti K -edge of a SrTiO3 single crystal under uniaxial pressure were measured to obtain evidence of uniaxial pressure-induced polarization predicted in SrTiO3 from the electronic viewpoint. The pre-edge 3 d - e g peak decreases in intensity with increasing uniaxial pressure, together with an energy shift to higher energy side. Contrary to uniaxial deformation, these changes were independent of incident x-ray polarization. This implies the presence of a mechanism that maintains the isotropic coordination environment around a Ti atom, i.e. a tilt and rotation of the TiO6 octahedron accompanied by its isotropic shrinkage, hence the local polarization essential to the ferroelectric order cannot be observed.